2013
DOI: 10.3171/2013.1.jns12559
|View full text |Cite
|
Sign up to set email alerts
|

Targeting accuracy of transcranial magnetic resonance–guided high-intensity focused ultrasound brain therapy: a fresh cadaver model

Abstract: Despite its limits (temperature, vascularization), the human cadaver model is effective for studying the accuracy of MRgHIFU brain therapy. With the 1-MHz system investigated here, there is millimetric accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 31 publications
2
54
0
Order By: Relevance
“…This is in agreement with previous studies which have demonstrated that good spatial targeting of HIFU can be obtained via simulated TR using relatively coarse spatial sampling. 11,30 Homogeneous testing demonstrated total convergence across all metrics by 3.5 PPW, which is to be expected given the behavior of the PML and BLI, discussed in Sec. III.…”
Section: Convergence Testing In 3dsupporting
confidence: 62%
See 4 more Smart Citations
“…This is in agreement with previous studies which have demonstrated that good spatial targeting of HIFU can be obtained via simulated TR using relatively coarse spatial sampling. 11,30 Homogeneous testing demonstrated total convergence across all metrics by 3.5 PPW, which is to be expected given the behavior of the PML and BLI, discussed in Sec. III.…”
Section: Convergence Testing In 3dsupporting
confidence: 62%
“…For high-intensity thermal applications, model-driven TR may be combined with MRI thermometry for treatment verification. Chauvet et al 11 confirmed the potential for model-driven TR-based focusing inside the human head to millimeter precision, verified by MRI thermometry. Marquet et al 12 showed that model-driven TR is capable of restoring 90% of the peak pressure that can be obtained with gold-standard hydrophone based methods when focusing through an ex vivo skull bone.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations